POTENSI KEWIRAUSAHAAN MAHASISWA DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS UDAYANA - Satrya, I Gusti Bagus Honor; Suwandana, I Gusti Made (E-Jurnal Manajemen; Vol 4 No 12 (2015), 2015)
This research is developed to understand the potential of student entrepreneurs and to evaluate the factors that can influence potential student becoming entrepreneurs at the Faculty of Economics and Business at Udayana University. The data of this research is gathered through the use of questionnaires that are given to students as the main respondents of this research in which are 99 (nintynine students) from various categories of entry years, gender types and programs. The data that has been gathered is analyzed using a ‘Diskriptive Statistic’ that is analyzed to provide a broad picture or an empirical description of potential students becoming entrepreneurs. The data in this research is developed to create a scoring system for every question within the questionnaire by using an average that is based upon a relative load factor. The implications of this research are based upon the potential of students having significant influence in development of skills in the entrepreneurial sector. From this the increase and development of potential student entrepreneurs can provide a contribution which is positive in the application of operations and success of the student enpreneur individually.
Keywords: Potential, Entrepreneur, Students